SHI irradiation induced effects in functionalized MWCNTs - Saikiran, V.; Pathak, A. P.; Rao, N. Srinivasa; Devaraju, G.; Debgupta, Joyashish; Kyriakou, I.; Emfietzoglou, D. (Radiation Effects and Defects in Solids, 2012)
Multi-walled carbon nanotubes (MWCNTs) have attracted extensive attention globally due to their applications in modern nanotechnology. It is very important to study the effects on these MWCNTs under swift heavy ion (SHI) irradiation since ion irradiation has been recognized as one of the best tools for nanostructuring of materials, in general. Here, we present the effects of 80MeV Ni ions with a fluence ranging from 3 x 10(12) to 3 x 10(13) ions/cm(2) on functionalized MWCNT mats. The properties of pristine and irradiated samples were studied using X-ray diffraction, Raman spectroscopy and transmission electron microscopy. The effects of SHI irradiation on these samples are discussed in detail.
Keywords: CNT; Raman; SHI; TEM

Synthesis of novel Cu2S nanohusks as high performance counter electrode for CdS/CdSe sensitized solar cell - Kamaja, Chaitanya Krishna; Devarapalli, Rami Reddy; Dave, Yasha; Debgupta, Joyashish; Shelke, Manjusha V. (Journal of Power Sources, 2016)
An important component of quantum dot sensitized solar cells (QDSSC) is the counter electrode which mediates the regeneration of oxidized quantum dots by reducing the polysulphide electrolyte. However, design and synthesis of an efficient counter electrode material is a challenging task. Herein, we report the synthesis of a unique Cu2S nanohusks directly on FTO coated glass substrates by electrodeposition and used as a counter electrode in QDSSC. When these electrodes are used for the reduction of polysulfide electrolyte in QDSSC, they exhibit higher catalytic activity and photovoltaic performance as compared to the Platinum counter electrode. The power conversion efficiency of about 4.68% has been achieved by optimizing the deposition time of Cu2S. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: counter electrode; Cu2S electrodeposition; Cu2S nanohusks; Quantum dot-sensitized solar cell